2017
DOI: 10.1007/s00423-017-1629-y
|View full text |Cite
|
Sign up to set email alerts
|

2D vs. 3D imaging in laparoscopic surgery—results of a prospective randomized trial

Abstract: 3D imaging could be a possible advantage in laparoscopic surgery. The results of our clinical trial show increased personal felt safety and efficiency of the surgeon using a 3D imaging system. Overall of the procedures, the findings assessed using Likert scales in terms of own felt safety and task efficiency were statistically significant for 3D imaging. The individually perceived workload assessed with the Raw NASA TLX shows no difference. Although these findings are subjective impressions of the performing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 29 publications
1
11
1
1
Order By: Relevance
“…Compared to open procedures, thoracoscopically-supported vertebral body replacement allows, among other things, shorter hospitalization as well as reduced postoperative problems [18], which has led to the trend of minimally-invasive endoscopic treatment. In addition to 2D optics, the use of 3D optics has been increasingly used for endoscopic procedures in recent years, leading to the optimization of depth perception, precision and spatial orientation during laparoscopic surgery [4,6,11,14,16]. In our present study, there was also a trend toward shorter surgery time using 3D optics during thoracoscopic procedures, which, however, was statistically not significant.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…Compared to open procedures, thoracoscopically-supported vertebral body replacement allows, among other things, shorter hospitalization as well as reduced postoperative problems [18], which has led to the trend of minimally-invasive endoscopic treatment. In addition to 2D optics, the use of 3D optics has been increasingly used for endoscopic procedures in recent years, leading to the optimization of depth perception, precision and spatial orientation during laparoscopic surgery [4,6,11,14,16]. In our present study, there was also a trend toward shorter surgery time using 3D optics during thoracoscopic procedures, which, however, was statistically not significant.…”
Section: Discussioncontrasting
confidence: 53%
“…In their patient cohort (3D laparoscopic hysterectomy), Berlit et al observed significantly lower blood loss and shorter operating times compared to the 2D group [15]. A further explanation for reduced blood loss using 3D optics is improved precision, more efficient and rapid surgical hemostasis [6,7,15,16].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, this improvement comes with increased eye strain, headache, and other visual symptoms. 23,24 The literature [25][26][27][28] has evaluated the consequences of 3-D imaging systems in laparoscopic surgery, but prospective data are limited, lacking robust objective evaluation criteria for technical performance or evaluation of clinically significant patient outcome measures. The purpose of this study was to compare the association of using 3-D vs 2-D imaging systems with technical performance and surgical safety while performing laparoscopic Roux-en-Y gastric bypass (LRYGB) procedures.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it is important to improve the quality of the images displayed on the monitor. The use of the 2K high‐definition endoscope (1920 × 1080 pixels) is widespread, but the 3‐D endoscope and 4K endoscope (3840 × 2160 pixels) have also recently been used in the clinical setting . We performed laparoscopic surgery for three cases of colorectal cancer using an 8K ultra‐high‐definition (UHD) endoscope (7680 × 4320 pixels) and assessed our clinical experience with this endoscope system.…”
Section: Introductionmentioning
confidence: 99%